A call for lifelong follow-up in CDH: identifying recurrence patterns and the importance of routine monitoring - Klinke Petrowsky, Michaela; Weis, Meike; Martel, Richard; Mohr, Christoph; Boettcher, Johannes; Ledermann, Yannick; Thees, Patrick; Schaible, Thomas; Kipfmüller, Florian; Boettcher, Michael; Elrod, Julia (Journal of pediatric surgery, 2026)
Background - Congenital diaphragmatic hernia (CDH) is a severe developmental disorder characterized by pulmonary hypoplasia and pulmonary hypertension, leading to high neonatal morbidity and mortality. Despite improved survival, recurrence remains a relevant long-term complication, presenting either asymptomatically during follow-up or as acute emergencies. Understanding recurrence patterns, risk factors, and management is essential for optimizing outcomes. - Methods - Children undergoing surgical CDH repair between 2000 and 2023 were analyzed. Demographic, treatment, and follow-up data were collected. Recurrence was defined by imaging or clinical detection of post-repair diaphragmatic defects. Timing, clinical presentation, and management were recorded, and potential risk factors were evaluated. The role of routine surveillance in early detection was assessed. - Results - Among 1247 treated children, 104 recurrences were identified (8.3 %; 10.8 % of survivors). Median age at recurrence diagnosis was 398 days (range 11-6188); 66.7 % occurred by two years of age. At diagnosis, 34.5 % were asymptomatic, 29.9 % had respiratory symptoms and 25.3 % vomiting. Intraoperative complications such as ileus or volvulus occurred in 14.7 % of surgically managed cases and were consistently diagnosed by severe radiologic signs. Risk factors included intrathoracic liver position (p = 0.0089), left-sided defects (p = 0.0072), large defect size (p = 0.0343), low birth weight (p = 0.0037), and lower gestational age (p = 0.0389). In 60.0 % of surgically treated recurrences, an additional patch was required. - Conclusion - CDH recurrences occur across all ages and often remain asymptomatic. Structured lifelong follow-up facilitates early detection and intervention, preventing severe complications. These findings support routine surveillance and the establishment of standardized long-term care protocols.